MicroRNA profiling in aplastic anemia reveals similarities between secondary myelodysplastic syndromes arising from clonal progression and de novo MDS - Chee, Lynette; Koldej, Rachel; Thio, Niko; Ludford-Menting, Mandy; Fox, Lucy; Blombery, Piers; Ritchie, David (Frontiers in Hematology, 2023)
Aplastic anemia (AA) is a form of bone marrow failure (BMF) resulting in significant cytopenias and may progress with clonal evolution to myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). MicroRNA expression is dysregulated in MDS/AML, but there are limited studies on its role in the pathogenesis of AA. Using stored bone marrow (BM) samples (n=81) from 52 patients collected between 2006 and 2019, we demonstrate key differences in miRNA expression between AA patients at diagnosis and de novo MDS patients (n=21). The five most significantly upregulated miRNAs in MDS patients (downregulated in AA) were miR-130a-3p, miR-221-3p, miR-126-3p, miR-27b-3p, and miR-196b-5p (adjusted p<0.001). However, at the time of AA clonal progression to secondary MDS/AML, no significant miRNA-based differences were identified, suggesting that the underlying mechanistic pathways between AA progression to MDS/AML and de novo MDS are similar. At diagnosis, miR-127-3p, miR-1271-5p, miR-301b-5p, miR-3934-5p, and miR-4531 (adjusted p=0.081) were upregulated in those whose AA eventually progressed in comparison with those without eventual clonal progression. Longitudinal molecular mutational analysis of myeloid genes in AA patients with disease progression revealed the acquisition of new mutations, mostly at the time of MDS/AML progression, with four patients developing mutations prior to morphological MDS progression. In contrast, no myeloid gene mutations were detected at diagnosis or follow-up in AA patients with no clonal progression. Using KEGG pathway analysis derived from miRPathDBv2.0, cytokine–cytokine receptor interaction, TGF-β, MAP kinase, prolactin, Hippo, neurotrophin, and FOXO signaling pathways were enriched in AA patients with clonal progression to MDS/AML; these pathways were similarly enriched in the de novo MDS cohort. These studies highlight the differing miRNA expression profiles in AA and MDS, in AA clonal evolution to MDS/AML, and the potential interplay with myeloid gene mutations acquired at the time of disease progression.